2016
DOI: 10.1088/1748-9326/11/6/064004
|View full text |Cite
|
Sign up to set email alerts
|

Green and cool roofs to mitigate urban heat island effects in the Chicago metropolitan area: evaluation with a regional climate model

Abstract: The effects of urban heat islands (UHIs) have a substantial bearing on the sustainability of cities and environs. This paper examines the efficacy of green and cool roofs as potential UHI mitigation strategies to make cities more resilient against UHI. We have employed the urbanized version of the Weather Research and Forecasting (uWRF) model at high (1 km) resolution with physically-based rooftop parameterization schemes (conventional, green and cool), a first-time application to the Chicago metropolitan area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
114
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(139 citation statements)
references
References 60 publications
(53 reference statements)
13
114
1
Order By: Relevance
“…WRF has multiple parameterizations for its physics components: microphysics, convection, radiation, boundary layer, and surface. Previous studies identified the following combination of physical parameterizations over Chicago (Smith and Roebber, ; Sharma et al , , ; Conry et al , ). We utilized a four‐layer Noah land surface model (LSM: Chen and Dudhia, ).…”
Section: Experimental Design and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…WRF has multiple parameterizations for its physics components: microphysics, convection, radiation, boundary layer, and surface. Previous studies identified the following combination of physical parameterizations over Chicago (Smith and Roebber, ; Sharma et al , , ; Conry et al , ). We utilized a four‐layer Noah land surface model (LSM: Chen and Dudhia, ).…”
Section: Experimental Design and Methodsmentioning
confidence: 99%
“…Land features and land‐use, including terrain (Sharma and Huang, ), streets and buildings, building materials, vegetation, and anthropogenic heat (AH) sources (among many other factors) exert strong controls on UHI effects. Some examples are the proximity to ocean, sea, or lake (Chen et al , ; Salamanca et al , ; Sharma et al , ), type of vegetation and land‐cover (Georgescu et al , ; Sharma et al , , ), presence of streets, buildings, parking lots, residential versus commercial development, city morphology (e.g. horizontal vs vertical structure of buildings), surface albedo (Vahmani and Ban‐Weiss, ), types of construction materials (Santamouris et al , ), and sources of AH [e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its volume, studies of spatialization of the differences between intra-urban and rural temperatures can contribute to mitigate the magnitude of UHIs [17,18] and improve quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…ODLI et al [2016] study results also showed the green roof reduced the indoor average temperature 2.4°C. Different researchers [ARABI et al 2015;LI et al 2014;SHARMA et al 2016;SHISHEGAR 2014] from all around the world studied green roof for the temperature reduction within an area. SHARMA et al [2016] used the regional climatic model at Chicago, USA to evaluate the green roof performance to control the heat island phenomena.…”
Section: Introductionmentioning
confidence: 99%